ALIH KODE DAN CAMPUR KODE PERCAKAPAN MAHASISWA DI PERPUSTAKAAN UNIVERSITAS PEKALONGAN - Erwan Kustriyono; M. Chamdi Rochmat (LPPM Universitas Pekalongan, 2013)
Language is the most effective tool in the delivery of the message to others or hearer. The use of language in the conversation appears a message which is conveyed to the opponent's speakers said. Conversations involving speakers and hearer will bring up the code-switching and code-mixing. These codes appear in the conversation conducted by University students that occurred in Pekalongan University library. There are many factors that affect the transfer of those codes. The factors that cause dominant code- switching in conversation at the library of the Pekalongan University are that the hearer factors and subject. Meanwhile, the dominant linguistic elements of code-mixing obtained in the conversation in the library of the Pekalongan University is the intangible elements of the inserted words and inserted phrases. Keywordsi: code-switching, code-mixing and conversation